+0  
 
0
56
1
avatar

 

 

I know I posted this question yesterday but I really nead help on it urgently

 

 

Thank You

Guest Dec 2, 2017
Sort: 

1+0 Answers

 #1
avatar+91237 
+1

Here you go:

 

\(\frac{p(x)}{x-2}=(x+1)q(x)+\frac{Ax+B}{x-2}\\ \frac{p(x)}{x-2}=(x+1)q(x)+A+\frac{B+2A}{x-2}\qquad \text{Note: I used algebraic division here}\\ where\;\;B+2A=3\qquad (1)\\~\\ \frac{p(x)}{x+1}=(x-2)q(x)+\frac{Ax+B}{x+1}\\ \frac{p(x)}{x+1}=(x-2)q(x)+A+\frac{B-A}{x+1}\\ where\;\;B-A=9 \qquad (2)\)

 

Solve (1) and (2) simultaneously and you get A=-2 and B=7

 

so

\(p(x)=(x-2)(x+1)q(x)-2x+7\\ \frac{p(x)}{(x-2)(x+1)}=q(x)\;\;Remainder\;-2x+7\\\)

Melody  Dec 3, 2017

34 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details